2015
DOI: 10.3748/wjg.v21.i36.10299
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis C virus infection and lipoprotein metabolism

Abstract: Hepatitis C virus (HCV) is a hepatotrophic virus and a major cause of chronic liver disease, including hepatocellular carcinoma, worldwide. The life cycle of HCV is closely associated with the metabolism of lipids and lipoproteins. The main function of lipoproteins is transporting lipids throughout the body. Triglycerides, free cholesterol, cholesteryl esters, and phospholipids are the major components of the transported lipids. The pathway of HCV assembly and secretion is closely linked to lipoprotein product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 135 publications
2
51
0
Order By: Relevance
“…Nevertheless, a widely accepted description of the putative structural organisation of LVPs has been published, depicting a hybrid particle consisting of lipoprotein and HCV components sharing a common envelope2 (figure 2E). However, this model has never been validated by TEM images of viral particles originating from a physiological sample, such as serum from an HCV+ patient.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a widely accepted description of the putative structural organisation of LVPs has been published, depicting a hybrid particle consisting of lipoprotein and HCV components sharing a common envelope2 (figure 2E). However, this model has never been validated by TEM images of viral particles originating from a physiological sample, such as serum from an HCV+ patient.…”
Section: Discussionmentioning
confidence: 99%
“…HCV particles in the peripheral blood are coated with lipids. About 10 8 HCV particles are assumed to be secreted from the liver into peripheral blood every 24 h[14]. This finding suggested that lipid metabolism is somewhat shifted towards the production of HCV particles.…”
Section: Introductionmentioning
confidence: 99%
“…Lipoproteins all have a common structure, consisting of a single outer layer of phospholipids, free cholesterol and amphipathic proteins that surrounds a non-polar core composed of triglycerides, cholesterol esters and fat-soluble components such as vitamins [5, 7]. The structure of a VLDL is illustrated in Figure 1.…”
Section: Focus On Lipoproteins Metabolismmentioning
confidence: 99%
“…Approximately 50% of IDL are cleared from the circulation through their interaction with hepatic remnant receptors and LDLR, while the remaining IDL can undergo further catabolism by the hepatic lipase (HL) to become LDL through the loss of ApoE. LDL have a high cholesterol content and provide cholesterol to peripheral tissues or liver cells via interaction of ApoB-100 with LDLR [7, 8]…”
Section: Focus On Lipoproteins Metabolismmentioning
confidence: 99%